Conceptual design evaluation of concurrent brake actuator mechanism / Mahamad Hisyam Mahamad Basri … [et al.] - Mahamad Basri, Mahamad Hisyam; Zulkifli, Abdul Halim; Ismail, Noor Iswadi; Ab Hamid Pahmi, Muhammad Arif; Azmi, Husin (Smart Manufacturing Research Institute (SMRI), 2021)
The proper amount of braking force on both wheels is needed to optimize the braking performance and stability of the motorcycle. The braking effectiveness can be maximized by keeping the ideal nonlinear brake force distribution during braking. Thus the purpose of this research is to Present a mechanism that can be accommodated as a Concurrent Brake Actuator (CBA) design to control the ideal nonlinear brake force distribution. In this paper, the conceptual design of the CBA mechanism is developed to be used as a based design for CBA development. Thus, two conceptual designs of the CBA mechanism have been generated. The proposed concept designs were evaluated based on Design Failure Mode and Effect Analysis (DFMEA) and SOLIDWORKS Motion Analysis. The potential failure of the CBA concept design was determined based on the risk priority number (RPN) in DFMEA. The information obtained from DFMEA was used in SOLIDWORKS Motion Analysis to identify stress performance analysis for each CBA conceptual design. Then, the best CBA concept design will be selected. The selection was made based on the highest score gained by the CBA concept design in qualitative evaluation. Based on the results, the fixed main body design with a tilted position linear slope in CBA Design is potentially to actuate and distribute the nonlinear brake force to the front and rear brake with less potential of failure. Therefore, the proposed mechanism design will be used as a based mechanism design for CBA development.